Vokale Ausdrucksmuster im Kontext von Star-Images und kulturellen Stereotypen : eine exemplarische Analyse der Vokalstile von Bert Williams und Bing Crosby - Hähnel, Tilo; Justus Liebig University Giessen (My University, 2014)
Assuming that star images are interrelated with cultural stereotypes, the present article analyses vocal expression as a means to shape both, images and stereotypes, and control their relationship. An investigation into the vocal style of blackface comedian Bert Williams exemplifies how vocal expression counterpoints a stage persona in a way that allows the star persona to shine through. Bing Crosby is used as a second example to show how vocal expression is related to star images and stereotypes when both are defined ex negativo and characterised as being »normal«.
Keywords: ddc:780